Experimental and Computer Analyses of Impact Penetration of a Steel Rod into Heavy Plates Of Steel and Aluminum Alloys - Kruszka, L.; Stepanov, G.V.; Kharchenko, V.V.; Zubov, V.I. (Engineering Transactions, 2004)
In the paper some results of experimental and numerical analysis concerning penetration of a steel rod (with conical and flat-faced heads) into heavy high-strength steel and AlMg6, Al-Zn-Mg and D16 aluminum alloys plates are presented. The calculations are conducted for relatively Iow velocities of penetration (200–1000 m/s), so the hydrodynamic component of the pressure on the contact surface is much lower than the strength of the material with allowance for viscosity effects. In most variants, the strains in the rod are assumed to be elastic for revealing effects of viscosity of the plate material. The resistance to penetration at its initial stages (prior to the rod plastic flow and fracture) is found to be determined by the dynamic strength of the plate material, its viscous component (proportional to the plastic strain rate) prevailing at the impact velocities of up to 500 m/s. From the experimental analysis it follows that the depth of penetration varies with the resistance, and it is conditioned by wave processes in the plate, their scale being dependent on its thickness. Such experimental results are in agreement with results of computer simulation of the initial stage of rigid rod penetration in plates of limited thickness.